2011
DOI: 10.1097/jom.0b013e3182337778
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and Workplace Policies Predict Smoking Behaviors

Abstract: Objective Describe differences in smoking behaviors associated with occupation, workplace rules against smoking, and workplace smoking cessation programs. Methods We analyzed data from the Current Population Survey- Tobacco Use Supplement surveys from 1992 through 2007. Results After adjusting for demographic factors, blue-collar workers were at higher risk than white-collar workers for ever smoking, current smoking, and persistent smoking (current smoking among ever smokers). Construction workers were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 12 publications
4
67
3
Order By: Relevance
“…12,13 Low salaries, insecure employment and weak interpersonal relationships are characteristics of casual, temporary employment 19 and are associated with greater vulnerability to harmful habits such as smoking. 10 It is probable that the occupational characteristics of the group analyzed (admission by public contest, job stability, guaranteed health insurance and health care, internal regulation of tobacco consumption and physical activity) explain the lower prevalence of smoking found here compared with general population surveys.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…12,13 Low salaries, insecure employment and weak interpersonal relationships are characteristics of casual, temporary employment 19 and are associated with greater vulnerability to harmful habits such as smoking. 10 It is probable that the occupational characteristics of the group analyzed (admission by public contest, job stability, guaranteed health insurance and health care, internal regulation of tobacco consumption and physical activity) explain the lower prevalence of smoking found here compared with general population surveys.…”
Section: Discussionmentioning
confidence: 74%
“…7 Anti-smoking measures occur at various levels, 21,22 among which, the advantages of actions developed in the locus of work are recognized. 10 There is evidence of the association between occupational stressors and smoking. 1,2,8,11 Twofold exposure is recorded in the emergency sector:…”
mentioning
confidence: 99%
“…Furthermore, participants who worked in the service industry had higher rates of exposure (74%) in our study compared to a previous study (50%, Wakefield et al, 2005). Previous research has found those employments with fewer smoking restrictions or formal policies also have the highest rates of ETS exposure and the fewest resources for offering cessation assistance for employees (Uslan, Forster, & Chen, 2007; Ham et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Compared to college graduates, those with less than a high school education are more than 4 times as likely to smoke (Hughes et al, 2010). Among employed adults who participated in the 2006-2007 Current Population Survey – Tobacco Use Supplement, those in blue-collar occupations are at higher risk than those in white-collar occupations for current smoking (Ham et al, 2011). Moreover, construction workers are more likely to be current daily smokers than other blue-collar workers (Ham et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among employed adults who participated in the 2006-2007 Current Population Survey – Tobacco Use Supplement, those in blue-collar occupations are at higher risk than those in white-collar occupations for current smoking (Ham et al, 2011). Moreover, construction workers are more likely to be current daily smokers than other blue-collar workers (Ham et al, 2011). It should be noted that females accounted for only 3% of construction workers in this national sample.…”
Section: Introductionmentioning
confidence: 99%